2015
DOI: 10.1080/14702541.2015.1068947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating New Digital Technologies Through a Framework of Resilience

Abstract: This paper explores how an evaluative framework of resilience might be utilised to assess the impact of new digital technologies. This paper outlines key themes and indicators from recent literature on community-level and rural resilience and incorporates insights from work on digital inclusion and rural information and communication technologies to build a framework of rural community resilience. It then highlights a successful case study carried out by the Digital Engagement and Resilience project and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
(42 reference statements)
1
26
0
1
Order By: Relevance
“…In some cases, the financing was the subject of discussions, but according to the community group representatives, any problems that arose were minor. Similar tensions between what was defined as 'individual resilience' and what was defined as 'community resilience' occurred in a study of rural broadband development in Scotland (Roberts et al 2015). In Linköping Municipality some of the community groups were legally created especially for the broadband expansion, which also put some strain on how the boundaries were constructed:…”
Section: Involvement Of Non-profit Community Groupsmentioning
confidence: 87%
See 3 more Smart Citations
“…In some cases, the financing was the subject of discussions, but according to the community group representatives, any problems that arose were minor. Similar tensions between what was defined as 'individual resilience' and what was defined as 'community resilience' occurred in a study of rural broadband development in Scotland (Roberts et al 2015). In Linköping Municipality some of the community groups were legally created especially for the broadband expansion, which also put some strain on how the boundaries were constructed:…”
Section: Involvement Of Non-profit Community Groupsmentioning
confidence: 87%
“…An extensive study of the relationship between broadband expansion and economic growth in the USA supported this conclusion, and showed that availability was less important than adoption in terms of subscribing to broadband services (Whitacre et al 2014). Some recent studies have identified increased opportunities for creative rural businesses that have been opened up by ICT adoption (Roberts et al 2015;Anderson et al 2016).…”
Section: Ict Development In Rural Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…supporting digital health and digital inclusion T he rural-urban divide is widely associated with lower health status, reduced access to health, transport, technology and education and stifled economic growth (Reed et al, 2014;E. Roberts et al, 2015).…”
mentioning
confidence: 99%